De la Renaissance à la Restauration : quelques étapes du déchiffrement des hiéroglyphes - Dominique Farout (Les Cahiers de l'École du Louvre)
Deciphering Egyptian hieroglyphs is not the miraculous achievement of one isolated genius, but rather the result of a long quest which covered several centuries and involved many scholars. Its origin dates back to the rediscovery of Antiquity during the Renaissance. Each one of these figures successively contributed to the project using the knowledge at their disposal at the time. In addition to this, some significant traditions from the Egyptian Middle Ages are at the root of fundamental concepts such as the link between Coptic and Pharaonic writing. Lastly, the discovery of the hieroglyphic system is the work of Champollion brothers, the elder guiding the younger: the latter did not simply decipher it all in an instant, one fine day in 1822.